Simbolisme Roti dan Air dalam Terang Logos: Analisis Metafisis dan Hermeneutis Injil Yohanes - Paula Leony Putri Terigas; Laurentius Prasetyo; Yanto Sandy Tjang (CV. ALIM'SPUBLISHING, 2026)
The study critically examines the Gospel of John as a theological text integrating the incarnate Logos and sacramental symbolism. Using a qualitative, library-based approach with historical-critical and hermeneutical analysis, it shows that John’s Gospel not only narrates Jesus’ life but constructs a symbolic, existential, and transformative theological reflection. The Logos shifts from a metaphysical principle to a personal reality in history through the incarnation, enabling a concrete encounter between God and humanity. Within this framework, symbols such as water and bread function as media of revelation guiding individuals toward a living, relational faith experience. Furthermore, sacramental symbolism in the Gospel of John is ontologically grounded in the incarnation of the Logos. Faith is thus understood not merely as intellectual assent but as participation in divine life that transforms human existence. The integration of Christological and sacramental dimensions indicates that faith is holistic, encompassing spiritual, material, and relational aspects. Thus, the Gospel of John presents a theological vision of faith as a concrete and dynamic existential encounter, relevant for contemporary theological reflection.